DETERMINATION OF WORLD COMMODITY PRICES AND MACROECONOMIC VARIABLES ON THE MOVEMENT OF THE INDEKS HARGA SAHAM GABUNGAN (IHSG) IN INDONESIA - Trisna Caraka Putra Prima; Hastarini Dwi Atmanti (Indonesian Interdisciplinary Journal of Sharia Economics (IIJSE), 2026)
This study aims to analyze the influence of global commodity prices and macroeconomic variables on the Harga Saham Gabungan (IHSG) in Indonesia. The independent variables in this study include global gold price returns, global oil price returns, the Rupiah exchange rate against the US dollar, interest rate returns, and the money supply (M2) return. The dependent variable is the IHSG return. The data used is monthly time series data from January 2020 to December 2024, obtained from official publications of Bank Indonesia (BI). The analytical method used is multiple linear regression with a return model transformation. The results show that all independent variables simultaneously have a significant effect on the IHSG return. Partially, global oil price returns have a significant positive effect on the IHSG return, while the Rupiah exchange rate returns have a significant negative effect. Meanwhile, global gold price returns, interest rate returns, and the money supply return do not show a significant effect.